Physical Properties of Orange Peels Eco-enzyme: One way to Reduce and Recycle Waste and Environmental Problem - Kirana, Kartika Hajar; Budianto, Muhammad Abdillah; Pranatikta, Krishna Agra; Shafaria, Mileani; Agustine, Eleonora; Fitriani, Dini; Susilawati, Anggie; Hasanah, Mia Uswatun (Phi: Jurnal Pendidikan Fisika dan Terapan, 2022)
A high quantity of organic waste without proper waste management can endanger public health and environmental sustainability. To reduce the risk that can be caused by organic waste pollution, then there should be a solution. One of them is to make eco-enzyme. Eco-enzyme is a fermented solution from organic waste that can be used as floor cleaner, plant disinfectant, hand sanitiser, plant fertilizer, etc. A good eco-enzyme solution has special properties. One of them is the low-value power of Hydrogen (pH). In this study, other physical properties of eco-enzyme are analyzed. Eco-enzyme was produced from organic waste. Here, Sunkist orange peel and various mixtures of orange peel were used as the main materials of eco-enzyme. The eco-enzyme solutions were carried out for 33 days, accompanied by routine monitoring by reviewing physical parameters such as pH, Total Dissolved Solid (TDS), and Electrical Conductivity (EC) values. The results showed the characteristics of the eco-enzyme product by physical properties are the eco-enzyme has an acidic with a low pH value (<3.6) accompanied by high values of TDS (>1000 ppm) and EC (>1500mS/cm). The finding is TDS and EC have high value whereas usually high EC and TDS are owned by polluted liquids.